Pengelolaan dan Pemanfaatan Sumber Daya Alam di Desa Sojomerto Kecamatan Gemuh Kabupaten Kendal Perspektif Islam - Annurroin, Nur (ITB AAS INDONESIA Surakarta, 2026)
Natural resources are a gift from Allah SWT. Which is given to humans so that they can be managed and utilized properly and wisely for the prosperity of human life, therefore natural resources need to be preserved and maintained as well as possible. This research was conducted with the aim of integrating the values ​​of Islamic sharia principles in managing and utilizing existing natural resources. This study uses a qualitative research method with a descriptive approach. With descriptive research, researchers try to describe events and incidents that are currently the center of attention without being biased towards certain parties. The results of the study show that the management and utilization of natural resources in Sojomerto are required ethically in accordance with Islamic principles for sustainable development, where in Islam humans are required to maintain and also preserve nature for the welfare of humans themselves. In the management and utilization of Islamic principles, several principles are needed, namely the principle of Grace towards nature, the principle of Responsibility, the principle of Solidarity, the principle of Compassion and concern for nature